The Reality of The Iraqi Economy and Foreign Direct Investment - Kerah Kazar, Fadhel (Indonesian Journal of Humanities and Social Sciences, 2023)
One of the most important sources of financing in foreign investments is that it has a significant role as one of the components of economic growth and works to increase productivity in the economy, improve the employment rate, and provide new job opportunities and advanced scientific knowledge. In Iraq, public and private direct investments witnessed a significant decline due to economic, political and security factors, which negatively affected economic life. The research included the introduction, the research problem and its importance, and the first topic, which dealt with the concept of investment and its types. The second topic dealt with the reality of the Iraqi economy, while the third topic explained the extent of the Iraqi economy’s need for foreign direct investment.